2018
DOI: 10.1007/s00204-018-2192-1
|View full text |Cite|
|
Sign up to set email alerts
|

Polymyxin B causes DNA damage in HK-2 cells and mice

Abstract: Increasing incidence of multidrug-resistant bacteria presents an imminent risk to global health. Polymyxins are 'last-resort' antibiotics against Gram-negative 'superbugs'; however, nephrotoxicity remains a key impediment in their clinical use. Molecular mechanisms underlying this nephrotoxicity remain poorly defined. Here, we examined the pathways which led to polymyxin B induced cell death in vitro and in vivo. Human proximal tubular cells were treated with polymyxin B (12.5-100 μM) for up to 24 h and showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 56 publications
5
11
0
1
Order By: Relevance
“…The present literature highlights the key role of DNA damage, metabolic and inflammatory perturbations, oxidative stress, cell cycle arrest, apoptosis, and autophagy in polymyxin-induced death of renal tubular cells in vitro and in vivo. A recent study showed the formation of micronuclei and multilobed nuclei, chromosome mis-segregation, and genome instability in HK-2 cells and mouse kidneys after polymyxin B treatment ( Yun et al, 2018 ). Increased expression of kidney γ H2AX (phosphorylated H2A histone family member X) suggested persistent DNA damage in kidneys by polymyxins.…”
Section: Polymyxin Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The present literature highlights the key role of DNA damage, metabolic and inflammatory perturbations, oxidative stress, cell cycle arrest, apoptosis, and autophagy in polymyxin-induced death of renal tubular cells in vitro and in vivo. A recent study showed the formation of micronuclei and multilobed nuclei, chromosome mis-segregation, and genome instability in HK-2 cells and mouse kidneys after polymyxin B treatment ( Yun et al, 2018 ). Increased expression of kidney γ H2AX (phosphorylated H2A histone family member X) suggested persistent DNA damage in kidneys by polymyxins.…”
Section: Polymyxin Toxicitymentioning
confidence: 99%
“…Increased expression of kidney γ H2AX (phosphorylated H2A histone family member X) suggested persistent DNA damage in kidneys by polymyxins. A transient cell cycle arrest followed by continuation with unrepaired DNA damage was speculated as a result of checkpoint perturbations by polymyxin B treatment ( Yun et al, 2018 ). Intraperitoneal administration of colistin (16 mg/kg per day in two divided doses) caused the upregulation of CCNB1 and CDC2 genes in mouse kidneys, suggesting cell cycle arrest at the G2/M phase ( Eadon et al, 2013 ).…”
Section: Polymyxin Toxicitymentioning
confidence: 99%
“…In this process, there is a substantial intracellular accumulation of the drug which is mediated by the endocytic receptor, megalin, as well as other transporters [7]. The high intracellular concentration of polymyxins has been demonstrated in both human (HK-2) and rat (NRK-52E) kidney cells, which allowed experiments in animal and cell culture models to further explore this phenomenon [8,9]. The accumulation of polymyxins leads to drug-induced cell apoptosis which in turn results in decreased renal function and histopathological damage.…”
Section: Mechanisms Of Nephrotoxicitymentioning
confidence: 99%
“… 7 Abdelraouf et al 4 concluded that polymyxin B was saturable into the proximal renal tubular epithelial cells of pigs, and was mainly absorbed through the cell apical membrane, suggesting that the megalin transporter plays an important role in the uptake and accumulation of polymyxin B in the kidney of rats. According to the relevant literature, 6 , 15 polymyxin B-induced nephrotoxicity is related to DNA damage of related cells caused by the drug, resulting in chromosome segregation and genomic instability in cellular mitosis, as well as oxidative stress, mitochondrial damage, and changes in the lactate dehydrogenase activity of target cells, resulting in apoptosis and necrosis of renal proximal tubular epithelial cells. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%